Incidencia del estrés laboral en la salud mental en un docente de 35 años en tiempos de covid - Vargas Valle, Génesis Victoria (2021)
Occupational stress in the teaching professional, based on the multifaceted role that he plays, generates a great impact on his development as an individual both in the personal and professional fields. The objective of this study is to determine the incidence of work stress in mental health in a 35-year-old teacher in types of Covid of the Educational Unit "Diez de Agosto" of the Cantón Montalvo, applying a therapeutic scheme based on the Cognitive Therapy approach. -Behavioral. The line of research that consists of psychological counseling will be followed, and as a sub-line the investigation called educational, personal, family, vocational and professional counseling and orientation, for which psychological techniques were applied: Clinical Observation, Clinical History, The Hamilton Anxiety Scale and Stress Vulnerability Test were also used, allowing the patient to be evaluated according to the case studied until a psychodiagnosis was obtained that would serve as the basis for carrying out the psychotherapeutic plan in this research topic. .